OJEK ONLINE DALAM BINGKAI HUKUM NASIONAL DAN SYARIAT ISLAM - Ihsan Helmi Lubis (Institut agama islam negeri Padangsidimpuan, 2022)
Ojek is one of the modes of transportation that existed since ancient times and is one of the transportation services of people/goods. In Indonesia there are 2 types of motorcycle taxi ojek both conventional and ojek online. The difference is if the motorcycle taxi online, consumers who order ojek service through a smartphone application that is connected to the internet and can be done anywhere either at home, office and so on, whereas if conventional motorcycle taxi can only be found when the consumer look for it at certain points. The purpose of this study is to answer the doubts of the public about the position of motorcycle tax law online both in terms of positive law applied in Indonesia as well as in terms of Islamic Law. The result of this research is that the motorcycle taxi is legally positive allowed or legalized by postprescription operated by President Joko Widodo. Meanwhile, if from the eyes of Islamic Law of ojek online is legalized for bringing goodness from society and country because it can reduce unemployment